Compensatory Feeding in Eastern Baltic Cod (Gadus morhua): Recent Shifts in Otolith Growth and Nitrogen Content Suggest Unprecedented Metabolic Changes - Svedäng, Henrik; Thunell, Viktor; Pålsson, Ale; Wikström, Sofia A.; Whitehouse, Martin J. (Frontiers in Marine Science, 2020)
The productivity of the Eastern Baltic cod (EBC) has been severely reduced over the last 25 years, for reasons that remain unclear. The size distribution of EBC has become increasingly truncated, condition and health status have deteriorated, and sexual maturation has started to occur at increasingly smaller sizes. Despite an increasing trend in recruitment during this period, reduced growth or increased mortality rates after the recruitment phase have resulted in decreasing landing levels and low profitability in the cod fishery, whereas the scientific community has difficulties in disentangling the causes of the decline of EBC. We studied changes in metabolic status in EBC between the capture years of 1995 and 2015, by investigating two aspects of fish metabolism that can be extracted retrospectively from otolith [earstone] morphometry and nitrogen content. Changes in relative otolith size to fish size are related to the metabolic history of the individual fish, and the otolith nitrogen content reveals the level of protein synthesis and feeding rate. Because otoliths accrue continuously on their surface and are biological stable (inert), the chemical content of the otolith trajectory reflects the timeline of the fish. We measured the N/Ca ratio as a proxy for protein content in EBC otolith along distal radius traverses from the core to the edge of the otolith by using secondary ion mass spectrometry (SIMS). Here we show that the otoliths have become smaller at a given fish size, and the ratio of N/Ca has increased over the studied period. These proxies reveal significant metabolic changes during the same period as the condition, and stock productivity has declined. We discuss potential mechanisms behind the metabolic changes, including elevated temperature and compensatory feeding due to nutrient deficiencies. Such changes in food quality may, in turn, relate to still unrecognized but on-going ecosystem shifts, where climate change could be the ultimate driver.